Nonlinear relationship between housing supply and house price in Malaysia - Yeap, Geok Peng; Lean, Hooi Hooi (International Journal of Strategic Property Management, 2020)
The novelty of this paper is to ascertain a nonlinear relationship between housing supply and house price. This study is conducted based on panel dataset of four different types of houses in Malaysia from 2002Q3 through 2016Q4. Although housing supply has been theoretically assumed to be positively and linearly related to house price, we observed that the number of new houses build in Malaysia has declined despite the increasing house prices. Hence, we posit that housing supply and house price are nonlinearly related. The results from pooled mean group estimation show the existence of inverted U-shaped housing supply curve. The threshold level of house price index is found at 186.92 where the effect of house price on housing starts will become negative after this point. We also find that the marginal effects of house price evaluated at the minimum and maximum levels are positive and negative, respectively, and statistically significant. This paper suggests that the squared term of house price should be included in estimating housing supply in Malaysia. The evidence of inverted U-shaped housing supply curve in Malaysia shows that housing authorities have taken steps to overcome the challenges of oversupply by reducing the approvals for housing development projects.First published online 23 July 2020